An unusual foreign body nose: a case report - Hippalgaonkar, Amruta V.; Pendharkar, Amod D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Nasal foreign bodies constitute an emergency and are more common in children with insertion generally via anterior nares. Case presentation: We present a case of 57-year-old-man with unusual entry site foreign body nose after external trauma to face, confirmed by 3D computed tomography and extracted through nasal route without any complication. Thus, nasal foreign bodies, a frequent accident in medical practice, usually harmless, but if neglected may cause complications hence prompt extraction is important.